Real Or Fake: Perspektif Mengenai Telur Setelah Adanya Berita Hoax - Ninda Ela Putri; Noerma Kurnia Fajarwati (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Information nowadays is easy to obtain because it is so easy Accessing. People are flooded with information from everywhere and from every medium. But this should be a very significant event. Because, The more information there is, the more it can be, the truth and the certainty. The public can freely express opinions and even share that message They can be to many people, whether the message is true or not. It is Causes deliberate and intentional conflict between individuals or groups Make false news to provoke. This work raises the subject of issues Hoax news circulating in society is commonly referred to asa hoax. Hoax moment It's become a very famous phenomenon these days. All kinds Information can easily be encountered without being researched. In this case The author has finally taken up a rather alarming issue of "fake eggs." Writer Creating a narrative of fact and fiction, choosing to play it in reality or not in space The scope of the communication process with audiences presented through installation artwork.